2021
DOI: 10.1093/mnras/stab1562
|View full text |Cite
|
Sign up to set email alerts
|

The imprint of cosmic web quenching on central galaxies

Abstract: We investigate how cosmic web environment impacts the average properties of central galaxies in the Sloan Digital Sky Survey (SDSS). We analyse how the average specific star-formation rate, stellar age, metallicity and element abundance ratio [α/Fe] of SDSS central galaxies depend on distance from the cosmic web nodes, walls and filaments identified by DisPerSE. In our approach we control for galaxy stellar mass and local density differentiated between field and group environment. Our results confirm the known… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 112 publications
1
18
1
Order By: Relevance
“…This could imply that galaxies travelling along the filaments are experiencing a much milder RPS compared to those travelling across the filaments. This result, however, contrasts with the work of Castignani et al (2021) who found that the star formation, gas content and morphological properties of galaxies in cosmic filaments are at intermediate levels between galaxies in isolation and in clusters suggesting that filaments are dense enough to produce measurable environmental effects (see also Winkel et al 2021)). In a study of 24 jellyfish galaxies extracted from the GASP survey that do not reside in galaxy clusters, Vulcani et al (2021) found two star forming objects (M star < 10 9.1 M ) with ionised gas tails that could be associated to cosmic web stripping.…”
Section: Clusters Vs Groups and Other Environmentscontrasting
confidence: 82%
“…This could imply that galaxies travelling along the filaments are experiencing a much milder RPS compared to those travelling across the filaments. This result, however, contrasts with the work of Castignani et al (2021) who found that the star formation, gas content and morphological properties of galaxies in cosmic filaments are at intermediate levels between galaxies in isolation and in clusters suggesting that filaments are dense enough to produce measurable environmental effects (see also Winkel et al 2021)). In a study of 24 jellyfish galaxies extracted from the GASP survey that do not reside in galaxy clusters, Vulcani et al (2021) found two star forming objects (M star < 10 9.1 M ) with ionised gas tails that could be associated to cosmic web stripping.…”
Section: Clusters Vs Groups and Other Environmentscontrasting
confidence: 82%
“…A gro wing body of e vidence sho ws that largescale filaments play a similar role in shaping the properties of galaxies as clusters do, albeit to a lesser degree. Galaxies close to cosmic web filaments are redder (Kraljic et al 2018 ;Laigle et al 2017 ), elliptical (Kuutma, Tamm & Tempel 2017 ), with higher metalliciy (Darvish et al 2015 ;Gray et al 2009 ), more massi ve (Malav asi et al 2016 ) and more likely to have been quenched (Alpaslan et al 2016 ;Winkel et al 2021 ) than their counterparts at fixed M * at increased distances away from filaments. This can be due to ram pressure that remo v es the hot haloes especially of lower mass galaxies (Bah é et al 2013 ;Ben ítez-Llambay et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…To extract cosmic web filaments in each volume of our sample at 𝑧 = 0, we used the robust filament finding algorithm D P SE (Sousbie 2011). We have applied the software on a discrete point distribution of mock galaxies in 3D and 2D -a useful and well established approach in both simulated and observed datasets across scales from sub-galactic to cosmological interests (e.g., Malavasi et al 2016Malavasi et al , 2020Kraljic et al 2018;Hess et al 2018;Arzoumanian et al 2019;Winkel et al 2021). For our purpose, we define mock galaxies as all halos with masses 𝑀 halo > 3 × 10 10 ℎ −1 M (comparable to 𝑀 * > 3 × 10 9 ℎ −1 M 3 ) and use them as input to D P SE.…”
Section: Filament Identificationmentioning
confidence: 99%
“…A growing body of evidence shows that large-scale filaments play a similar role in shaping the properties of galaxies as clusters do, albeit to a lesser degree. Galaxies close to cosmic web filaments are redder (Kraljic et al 2018;Laigle et al 2017), elliptical (Kuutma et al 2017), with higher metalliciy (Darvish et al 2015;Gray et al 2009), more massive (Malavasi et al 2016) and more likely to have been quenched (Alpaslan et al 2016;Winkel et al 2021) than their counterparts at fixed M* at increased distances away from filaments. This can be due to ram pressure that removes the hot halos especially of lower mass galaxies (Bahé et al 2013;Benítez-Llambay et al 2013).…”
Section: Introductionmentioning
confidence: 98%